The impact of within and between occupational inequalities on people's justice perceptions towards their own earnings - Carsten Sauer; Peter Valet; Stefan Liebig (Deutsches Institut für Wirtschaftsforschung (DIW), 2013)
This paper investigates justice perceptions of employees towards their own earnings. Earnings are decomposed into three components: (1) In returns based on human capital endowments, (2) in returns based on individual residual differences and (3) in returns based on differences between occupations. The legitimacy of these earnings components is measured via the justice assessments of employees. Based on theoretical models from justice research and class theory it is hypothesized that earnings inequality resulting from human capital factors is evaluated as just, whereas residual inequality and occupational inequality are perceived as unjust. The hypotheses are tested by using data from a German longitudinal panel study (SOEP) of the years 2005 to 2011. These data allow studying changes of individual earnings and justice evaluations in a household panel over the time span of six years (with four biennial measurement points). The findings support our hypotheses indicating that losses or gains in earnings which are due to changes in human capital endowments do not affect justice perceptions of own earnings. Losses or gains stemming from changes of a person's earnings position within the occupational group or the position of a person's occupational group within the earnings hierarchy of a society, however, affect justice perceptions remarkably. Thus, we can show that justice evaluations of own earnings do not solely depend on compensation for individual investments but also on residual differences in earnings within and between occupational groups.
Keywords: 330; earnings inequality; fairness of earnings; decomposition of justice evaluations; group identification; panel regression